The Isyārī Tafsir Method of the Story of Moses and Pharaoh in Al-Baḥr al-Madīd Ibn 'Ajībah (Analysis of the Four Letters) - Hermansyah Hermansyah; Tayeb Lamnaouar; Sobari Sutarip; Umi Kulsum (ZAD Al-Mufassirin, 2026)
This article examines the isyārī interpretation of the story of Prophet Moses and Pharaoh in several Qur’anic passages, namely Q.S. al-Qaṣaṣ [28]: 3–8, Q.S. al-Qaṣaṣ [28]: 15–21, Q.S. al-Shu‘arā’ [26]: 18–29, and Q.S. Yūnus [10]: 90–92 as interpreted in Al-Baḥr al-Madīd fī Tafsīr al-Qur’ān al-Majīd by Ibn ‘Ajībah. Using a qualitative method with a library research approach, this study explores the spiritual dimensions embedded in Ibn ‘Ajībah’s isyārī interpretation. The findings show that Ibn ‘Ajībah interprets these verses not only as historical narratives about the interaction between Moses and Pharaoh but also as symbolic representations of the spiritual struggle within the human soul. Pharaoh symbolizes arrogance and the domination of the ego, while Moses represents divine guidance that leads humans toward spiritual purification. This study highlights the contribution of isyārī interpretation in enriching the spiritual understanding of Qur’anic narratives and providing deeper spiritual reflection for readers.